2008
DOI: 10.1103/physrevb.77.045401
|View full text |Cite
|
Sign up to set email alerts
|

Trends in adsorption of noble gases He, Ne, Ar, Kr, and Xe onPd(111)(3×3)R30°: All-electron

Abstract: It was recently found from ab initio investigations ͓J. L. F. Da Silva et al., Phys. Rev. Lett. 90, 066104 ͑2003͔͒ that polarization effects and the site dependence of the Pauli repulsion largely dictate the nature of the interaction and the site preference of Xe adatoms on close-packed metal surfaces. It is unclear if the same interaction mechanism occurs for all rare-gas atoms adsorbed on such surfaces. To address this question, we perform all-electron density-functional theory calculations with the local-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
66
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 62 publications
15
66
1
Order By: Relevance
“…in particular, for Xe a general tendency is found [6,[8][9][10][11] for adsorption on metallic surfaces in the low-coordination top sites (this behavior is attributed [6,16] to the delocalization of charge density that increases the Pauli repulsion effect at the hollow sites relative to the top site and lifts the potential well upwards both in energy and height).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…in particular, for Xe a general tendency is found [6,[8][9][10][11] for adsorption on metallic surfaces in the low-coordination top sites (this behavior is attributed [6,16] to the delocalization of charge density that increases the Pauli repulsion effect at the hollow sites relative to the top site and lifts the potential well upwards both in energy and height).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the adatoms were adsorbed on both sides of the slab: in this way the surface dipole generated by adsorption on the upper surface of the slab is cancelled by the dipole appearing on the lower surface, thus greatly reducing the spurious dipole-dipole interactions between the periodically repeated images (previous DFT-based calculations have shown that these choices are appropriate [9,13,30,63]). …”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…is obtained, where A n ( k ) is defined through the boundary condition (27) which allows the calculation of G n+1 ( r, v ). After obtaining…”
Section: A Rough-surface Green's Functionmentioning
confidence: 99%